Wavelet Methods Used to Solve a System of Linear Equations - Riyad Mubarak Abdullah; Kais Ismail Ibraheem (College of Education for Pure Sciences, 2006)
In this paper, we study the comparison among many methods to solve a system of linear equations based on the principle of wavelet methods as a Daubechies wavelet, Haar wavelet, Meyer wavelet, Symlet wavelet, Mexican Hat wavelet, Morlet wavelet. As a result, the Haar wavelet method can be considered the best method to solve the linear equations compared with the other methods especially for the dense and sparse matrix. For the three diagonal matrices the Meyer wavelet gave a good results. Other conclusion was found that the Symlet wavelet needs a long time to solve this system of equations and for all types of the matrix.